Estimating yield in commercial wheat cultivars using the best predictors of powdery mildew and rust diseases - Naseri, Bita (Frontiers in Plant Science, 2022)
This four-year research determined the best predictors of black, brown and yellow rusts and powdery mildew development in different wheat cultivars and planting dates across 282 experimental field plots. Parameters estimated by exponential (black rust and powdery mildew) and Gaussian (brown and yellow rusts) models, area under disease progress curve (AUDPC), and maximum disease severity were considered as disease progress curve elements. Factor analysis determined the most predictive variables among 19 indicators to describe wheat yield. According to principal component analysis (PCA), 11 selected wheat diseases and yield predicators accounted for 60% of total variance in datasets. This PCA test described four principal components involving these selected predictors. Next, multivariate regression model developed according to four independent principal components justified a noticeable part of yield variability over and within growing seasons. Present findings may improve accuracy of future studies to examine seasonal patterns of powdery mildew and rusts, predict wheat yield and develop integrative disease management programs.